2021
DOI: 10.1371/journal.pone.0255906
|View full text |Cite
|
Sign up to set email alerts
|

An improved deep forest model for prediction of e-commerce consumers’ repurchase behavior

Abstract: As the Internet retail industry continues to rise, more and more consumers choose to shop online, especially Chinese consumers. Using consumer behavior data left on the Internet to predict repurchase behavior is of great significance for companies to achieve precision marketing. This paper proposes an improved deep forest model, and the interactive behavior characteristics of users and goods are added into the original feature model to predict the repurchase behavior of e-commerce consumers. Based on the Aliba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…The most powerful predictors of conversion behaviour are page and session stay time, user type, click entropy, and click position. The findings demonstrate that improved metrics and modelling approaches could yield significant gains in search behaviour [8].…”
Section: Literature Reviewmentioning
confidence: 86%
See 1 more Smart Citation
“…The most powerful predictors of conversion behaviour are page and session stay time, user type, click entropy, and click position. The findings demonstrate that improved metrics and modelling approaches could yield significant gains in search behaviour [8].…”
Section: Literature Reviewmentioning
confidence: 86%
“…Accuracy: The number of real positive tests compared to the total number of predicted benefits in Equation (8).…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…It takes a lot of time and effort. Zhang and Wang [29] developed an enhanced deep forest strategy for predicting consumer behavior, which is crucial for growing a firm. It is among the most crucial element of corporate intelligence.…”
Section: Literature Surveymentioning
confidence: 99%
“…In line with this, the Global Web Index has reported that a user typically makes use of social media for up to two hours and 42 minutes per day [6]. Therefore, the last decade has underlined social media marketing as an essential marketing tool, emerging as a mainstream research aspect [7].…”
Section: Introductionmentioning
confidence: 99%
“…To compare: consumers having the brand awareness orientation perceive the brand as a symbol of credibility and prestige, whereas those with value awareness usually check and compare the prices and quality of different brands through social media to ensure a best-value purchase [11]. To this end, many companies employ social media in carrying out low-cost and high-efficiency marketing activities for consumers [7,12]. Social media is a marketing tool wielded for four primary purposes: market research and feedback; brand promotion and reputation management; customer service and customer relationship management; and business network [13,14].…”
Section: Introductionmentioning
confidence: 99%